2000
DOI: 10.1023/a:1006396216933
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating dendritic/Langerhans cells in primary breast cancer

Abstract: It is fully anticipated that dendritic cells (DCs) will become a mainstay for inclusion in biological therapies for patients with cancer including breast cancer. To elucidate the cellular composition of DCs infiltrating human breast cancers, we investigated the correlations between the density of infiltrating DCs and some clinicopathological factors of breast cancer patients, examined cytokine expression on cancer cells and finally, assessed the numbers of CD45RO+ tumor infiltrating lymphocytes (TIL). Tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 36 publications
4
28
2
Order By: Relevance
“…This is in agreement with the previously reported effect of GM-CSF on migration of LHC/DC into organotypic cultures of HPV-transformed keratinocytes. 30 A similar positive correlation between the presence of GM-CSF, TNF-a, and the number of mature DC in breast cancer tissue was reported by Tsuge et al 31 In contrast, Trutmann et al 32 did not report a significant association between expression of GM-CSF and number of mature DC in colorectal cancer. A high level of TNF-a is known to induce migration of LHC to peripheral lymph nodes.…”
Section: Discussionsupporting
confidence: 54%
“…This is in agreement with the previously reported effect of GM-CSF on migration of LHC/DC into organotypic cultures of HPV-transformed keratinocytes. 30 A similar positive correlation between the presence of GM-CSF, TNF-a, and the number of mature DC in breast cancer tissue was reported by Tsuge et al 31 In contrast, Trutmann et al 32 did not report a significant association between expression of GM-CSF and number of mature DC in colorectal cancer. A high level of TNF-a is known to induce migration of LHC to peripheral lymph nodes.…”
Section: Discussionsupporting
confidence: 54%
“…The finding that activation was low or absent in tumour-associated DC populations in most breast cancers may have some bearing on the lack of apparent statistical association between CD1a and S-100 expression and survival. The observations that activated, mature DCs were restricted to a peritumoural location rather than within the tumour (Bell et al, 1999;Tsuge et al, 2000) imply that regional The association between CD1a and the NPI shows a nonsignificant (P ¼ 0.486) trend. Note that 20% of the patients with a higher CD1a density had a high (unfavourable) NPI, while 80% of the patients with a low CD1a density had an unfavourable NPI.…”
Section: Discussionmentioning
confidence: 99%
“…These findings show that the antitumour immune response in breast cancer is ineffective and that deficient DC function, at least in part, may be responsible for this (Coventry et al, 1996;Gabrilovich et al, 1997). The maturity and location of DC within breast tumours may not be uniform, such that more mature DCs, expressing differentiation/activation markers such as CD83, have been noted to be located peritumourally around the tumour mass, rather than infiltrating within it (Bell et al, 1999;Tsuge et al, 2000). Further recent data from two collaborative laboratories, using different methods and samples, demonstrated that the activation of DC was very low or absent within the breast cancer microenvironment using a variety of markers (Coventry et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, from the analyses of tumor specimens obtained from patients, a reduced number of DC infiltrated into tumors correlates with a poor prognosis for patients. 26,27) Also, the phenotypes and function of DC could be altered in tumors. DC infiltrated into tumor tissue showed a reduced expression of co-stimulatory molecules, defective cytokine production, and full allostimulatory activity, implying that tumor-derived factors impede DC maturation.…”
Section: Discussionmentioning
confidence: 99%